Development of Kitab Al Ajurumiyyah as Teaching Material with Additional HOTS (Higher Order Thinking Skills) Based Formative Tests at PP Al Fath Kediri - Afifuddin, Muhammad Haikal; Zunairoh, Yuyun; Moh Sholeh Afyuddin; M. Syamsul Ma’arif; Bagus Andrian Permata; Muhammad Abdur Rozaq (Naatiq: Journal of Arabic Education, 2024)
The book of Matan al Ajurumiyyah is one of the most famous nahwu books. However, in its development, the book used as teaching material needs additional components. One of them is the addition of evaluation. Learning nahwu in the book of Matan al Ajurumiyyah at PP Al Fath is carried out without evaluation. Based on these conditions, the researcher provided a solution by developing a learning evaluation book which containing formative test questions arranged according to the order of the chapters in the book of Matan al Ajurumiyyah. This research is development research or commonly known as (Research and Development) with the formulation of the problem of developing the book of Matan al Ajurumiyyah with the addition of HOTS-based formative test questions and the feasibility of HOTS-based formative test questions at PP Al Fath Kediri. This research aims to determine the development book of Matan al Ajurumiyyah with the addition of HOTS-based formative test items and the feasibility of HOTS-based formative test items at PP Al Fath Kediri. This development research uses the ADDIE research procedure. The population of this research were 30 Al Fath students who were randomly selected. The data collection methods used in this study were interviews, questionnaires, and tests. The result of this research is that a Nahwu Practice Questions from Matan al Ajurumiyyah. Based on the results of content expert validator and the construct of this book is of good quality with a percentage of 83.75% and based on the scores of media experts the appearance of this book is good with a percentage of 80%. From the expert validator, it was stated that the book was suitable to use with revision. In the product implementation, it was found that the highest student score was 94, the lowest score was 22, and the average student score was 67,6. The result of the item analysis questions were declared valid, because the questions measured students nahwu skills, and all questions were declared reliable because r = 0,793 > 0,70 for multiple choice questions and r = 0,95 > 0,70 for description questions.